Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a )
\(5x\left(x-3\right)+7\left(x-3\right)=0\)
\(\Rightarrow\left(5x+7\right)\left(x-3\right)=0\)
\(\Rightarrow\orbr{\begin{cases}5x+7=0\\x-3=0\end{cases}\Rightarrow\orbr{\begin{cases}5x=-7\\x=3\end{cases}\Rightarrow}\orbr{\begin{cases}x=-\frac{7}{5}\\x=3\end{cases}}}\)
Vậy ...
b )
\(x^{2017}=x^{2018}\)
\(\Rightarrow x^{2017}-x^{2018}=0\)
\(\Rightarrow x^{2017}\left(1-x\right)=0\)
\(\Rightarrow\orbr{\begin{cases}x^{2017}=0\\1-x=0\end{cases}\Rightarrow\orbr{\begin{cases}x=0\\x=1\end{cases}}}\)
Vậy ...
c )
\(2x^2=x\)
\(\Rightarrow2x^2:x=1\)
\(\Rightarrow2x=1\)
\(\Rightarrow x=\frac{1}{2}\)
Vậy ...
e )
\(x^5=x^4\)
\(\Rightarrow\orbr{\begin{cases}x=1\\x=0\end{cases}}\)( làm tương tự như phần b )
~
\(\frac{x-2}{2016}+\frac{x-3}{2017}+\frac{x-4}{2018}+3=0\)
\(\Leftrightarrow\left(\frac{x-2}{2016}+1\right)+\left(\frac{x-3}{2017}+1\right)+\left(\frac{x-4}{2018}+1\right)=0\)
\(\Leftrightarrow\frac{x+2014}{2016}+\frac{x+2014}{2017}+\frac{x+2014}{2018}=0\)
\(\Leftrightarrow\left(x+2014\right)\left(\frac{1}{2016}+\frac{1}{2017}+\frac{1}{2018}\right)=0\)
Mà \(\frac{1}{2016}+\frac{1}{2017}+\frac{1}{2018}\ne0\)
\(\Leftrightarrow x+2014=0\)
\(\Leftrightarrow x=-2014\)
Vậy \(x=-2014\)
Ta có : \(a^3+b^3+3\left(a^2+b^2\right)+4\left(a+b\right)+4=0\)
\(=>\left(a+1\right)^3+\left(b+1\right)^3+a+b+2=0\)
\(=>\left(a+b+2\right)\left[\left(a+1\right)^2-\left(a+1\right)\left(b+1\right)+\left(b+1\right)^2\right]+\left(a+b+2\right)=0\)
\(=>\left(a+b+2\right)\left(a^2+b^2+a+b-ab+2\right)=0\)
\(=>\left(a+b+2\right)2\left(a^2+b^2+a+b-ab+2\right)=0\)
\(=>\left(a+b+2\right)\left(2a^2+2b^2+2a+2b-2ab+4\right)=0\)
\(=>\left(a+b+2\right)\left[\left(a-b\right)^2+\left(a+1\right)^2+\left(b+1\right)^2+2\right]=0\)
Lại có : \(\left(a-b\right)^2\ge0;\left(a+1\right)^2\ge0;\left(b+1\right)^2\ge0\)
\(=>\left(a-b\right)^2+\left(a+1\right)^2+\left(b+1\right)^2+2\ge0\)
\(=>a+b+2=0=>a+b=-2=>M=2018.\left(-2\right)^2=8072\)
Giải các pt sau:
a) (x+4)(2x-3)=0
TH1: x+4=0 => x=-4
TH2 : 2x-3=0 => 2x=3 =>x=3/2
\(a+b+c=0\)
⇔\(\left(a+b+c\right)^2=0\)
⇔\(a^2+b^2+c^2+2\left(ab+bc+ca\right)=0\)
⇔\(2018+2\left(ab+bc+ca\right)=0\)
⇔\(ab+bc+ca=-1009\)
⇔\(\left(ab+bc+ca\right)^2=\left(-1009\right)^2=1009^2\)
⇔\(a^2b^2+b^2c^2+c^2a^2+2\left(ab^2c+abc^2+a^2bc\right)=1009^2\)
⇔\(a^2b^2+b^2c^2+c^2a^2+2abc\left(b+c+a\right)=1009^2\)
⇔\(a^2b^2+b^2c^2+c^2a^2=1009^2\)
\(a^2+b^2+c^2=2018\)
⇔\(\left(a^2+b^2+c^2\right)^2=2018^2\)
⇔\(a^4+b^4+c^4+2\left(a^2b^2+b^2c^2+c^2a^2\right)=2018^2\)
⇔\(a^4+b^4+c^4+2\cdot1009^2=2018^2\)
⇔\(a^4+b^4+c^4=2018^2-2\cdot1009^2=2036162\)
\(\dfrac{x+1}{2020}+\dfrac{x+2}{2019}+\dfrac{x+3}{2018}+\dfrac{x+4}{2017}+4=0\)
⇔ \(\dfrac{x+1}{2020}+1+\dfrac{x+2}{2019}+1+\dfrac{x+3}{2018}+1+\dfrac{x+4}{2017}+1=0\)
\(\Leftrightarrow\) \(\dfrac{x+2021}{2020}+\dfrac{x+2021}{2019}+\dfrac{x+2021}{2018}+\dfrac{x+2021}{2017}=0\)
⇔ \(\left(x+2021\right)\left(\dfrac{1}{2020}+\dfrac{1}{2019}+\dfrac{1}{2018}+\dfrac{1}{2017}\right)=0\)
\(Do\) \(\left(\dfrac{1}{2020}+\dfrac{1}{2019}+\dfrac{1}{2018}+\dfrac{1}{2017}\right)\ne0\)
⇒ \(x+2021=0\)
⇔ \(x=-2021\)
\(Vậy\) \(x=-2021\)
\(\left(-\frac{7}{4}\right)^2+\left(-\frac{3}{4}\right)^9.64-2018^0=\frac{49}{16}+\left(-\frac{19683}{262144}\right).64-1\)
\(=\frac{49}{16}-\frac{19683}{4096}-1\)\(=\frac{12544-19683-4096}{4096}\)
\(=-\frac{11235}{4096}\)